Using Crushed Limestone Rocks in Sports Field Rootzones at Different Levels of Bulk Density - Fattah, Mohammed Abdulrazzaq (Sulaimani Journal for Pure and Applied Sciences, 2016)
Most parks and sports fields are built using native type soils that generally contain excess clay and silt contents. Problems associated with these soil types include: easily compacted, poor drainage, low water infiltration, low nutrient availability, and reduced root growth. Various methods have been used to modify these soils by mixing it with sand and other amendments, due to shortage of natural sand in many parts of the world and conserving natural resources, it is necessary to find alternative materials; crushed limestone sand can be identified as an alternative natural sand in making good quality sport field mixture.To assess the possibility of using crushed limestone rocks and to establish a successful sports field mixture, (700, 270 and 30 g kg-1) of crushed limestone sand, native soil, andpeatmoss, respectively on mass basis were mixed. Some parameters that are related tosoil mixture of sport field were studied: stability, saturated hydraulic conductivity (Ksat), maximum water holding capacity (MWHC), and each of water holding capacity (WHC) against the gravity and penetration resistance (PRE) of mixture over time were measured at different bulk densities (1.2, 1.3, 1.4, 1.5 and 1.6 Mg m-3). To select the best bulk density (ρb) at constructed sports field rootzones, the coefficient of determination (R2) between ρb and each of the studied parameters were determined which were strong relation among them. This finding suggests that ρb may control problems during making soil mixture. In this research the best ρb of mixture are ranged from 1.417 to 1.510 Mg m-3 at which sports field soil provided good stability, good drain, and the quality of the playing surface well recognized in unfavorable weather conditions.
Keywords: Crushed limestone,Bulk density,Sability,Hydraulicconductivity,Penetrationresistance,Water holdingcapacity